The bee balm murders [large type] - Riggs, Cynthia (Riggs, Cynthia. Martha's Vineyard mysteries., 2011)
It's spring on Martha's Vineyard and at the suggestion of her beekeeper, Victoria Trumbull takes in a new boarder. Orion Nanopoulos is leading a project to lay a fiber-optic cable across the island. When a body is found in the trench where they are laying the cable, Orion recognizes the dead man as a potential investor. Victoria, renowned for her crime solving skills and for her knowledge of the island's residents, is hired by the victim's sons to investigate.